PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA HOTEL JAYAKARTA DAIRA PALEMBANG - Salman . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2013)
The Jayakarta Daira hotel is one ofÃ‚Â a kind stars hotel in palembang city, that moves on check in and serves for every guests to stay, and ofcourse the goals is to give the best service to the consumers with the facility sides, serving, and even for the prices. Consumers satisfaction is an evaluation of the most critical value that the hotel always be prepare to make the constumers feel the best services than they imagine. Although the costumers unsatisfaction show up if the result that the costumers hope more far from they really hope. So that,Ã‚Â to make it betterÃ‚Â the hotel should be more prepare from that situation to make it all the services in all kind of works in hotel more best for all costumers. And finally make the customers feel really serve after checking out. From the observation can be concludes that the quality of services can be attracting customers loyality to be more exiciting to the Jayakarta hotel palembang. It can be seen from the cooficience regression for variable of service quality is 0,309 also give a constanta point for 23,294 the same regression linear is Y= 23,294 + 0,309 X The result of cooficience correlation is 0,310 or 31%,Ã‚Â with this big result it is shows that there is a significant positive correlation between variable quality of service and costumers loyality, also with the cooficience of determination is 0,087. the result of testing hypotheses with t for the test, the result of thitungÃ‚Â Ã‚Â shows quality of service is 3,233 and for the value of sigtÃ‚Â the result is 0,002.Ã‚Â Key Word : Service quality, Customer Loyality Ã‚Â